Intracranial Rosai Dorfman Disease Presented With Multiple Huge Intraventricular Masses: A Case Report - Jamali, Elena; Sharifi, Guive; Ghafouri-Fard, Soudeh; Bidari Zerehpoosh, Farahnaz; Yazdanpanahi, Mahmood; Taheri, Mohammad (Frontiers in Surgery, 2022)
Introduction Rosai-Dorfman disease (RDD) usually presents with painless cervical lymphadenopathy during the two first decades of life, with or without extranodal involvement. Exclusive extranodal manifestation, and especially central nervous system (CNS) involvement, is uncommon. The etiology remains unknown and definitive diagnosis is based on characteristic histopathological and immunohistochemical features showing S100(+) CD1a(−) RDD type histiocytes with emperipolesis. Most CNS cases are dural-based masses. Case Presentation Herein, we present a case of RDD in an 8-year-old boy, who presented with multiple huge intraventricular masses. Conclusion Regarding rare CNS involvement and lack of established evidence-based therapeutic approaches, reports of any individual case can supply further beneficial data concerning treatment approaches and long-term effectiveness of therapeutic strategies.